The relationship between brain abnormalities and autistic psychopathology in pervasive developmental disorders - Efremova, Andrea; Lisy, Jiri; Hrdlicka, Michal (Journal of applied biomedicine, 2021)
The aim of the present research has been to determine whether there is a relationship between brain abnormalities found on magnetic resonance imaging (MRI) and autistic psychopathology. A retrospective analysis covering a period between 1998 and 2015 included 489 children with autism (404 boys, 85 girls; average age 8.0 ± 4.2 years) who underwent an MRI of the brain. For clinical diagnosis of autism, the International Classification of Diseases, 10th revision (ICD-10), was used. Autistic psychopathology was evaluated by means of the Autism Diagnostic Interview - Revised. The Spearman nonparametric correlation analysis and chi-square test were used to examine the possible relationships between variables. The group of autistic children did not manifest a statistically significant correlation between the parameters examined on MRI and autistic psychopathology. A correlation between other cysts and repetitive behavior was significant only at trend level (P = 0.054). Gliosis of the brain was significantly more frequent in autistic children with mental retardation than in children without mental retardation (14.1% vs. 7.4%; P = 0.028). Nonmyelinated areas in the brain were significantly more frequent in autistic children with autistic regression than in children without autistic regression (29.9% vs. 15.7%; P = 0.008). Mental retardation was significantly more frequent in autistic children with autistic regression than in children without regression (73.2% vs. 52.5%; P = 0.002). Our research study did not reveal a statistically significant correlation of brain abnormalities on MRI with autistic psychopathology.
Keywords: Developmental Disabilities; mozek; mužské pohlaví; Retrospective Studies; Male; retrospektivní studie; Humans; Female; Autism; autistická porucha; Autistic Disorder; MRI; Brain; lidé; ženské pohlaví; vývojové poruchy u dětí; mentální retardace; Psychopathology; Child; dítě; Child, Preschool; Intellectual Disability; předškolní dítě